Gut microbiome and bacterial resistance to antibiotics: reservoir or defence? - Vuković, Dragana (Medicinski podmladak, 2025)
Antibiotics have fundamentally transformed modern medicine, but their widespread use and misuse have led to the escalating crisis of antimicrobial resistance (AMR) in bacteria. Today, bacterial AMR represents a critical global health threat with severe medical and economic consequences. It is estimated that nearly five million deaths worldwide are linked to bacterial AMR each year. While vital for maintaining host health, the human gut microbiome also harbors a collection of antibiotic resistance genes (ARGs), collectively known as the gut resistome. Numerous studies have shown that the gut resistome serves as a reservoir for ARGs, which can be mobilized and transferred to both commensal and pathogenic bacteria through horizontal gene transfer. Antibiotic exposure is major factor that disrupts the diversity and function of the gut microbiome, leading to the proliferation of resistant bacteria and the accumulation of ARGs. These changes, in turn, facilitate the further spread of resistance among bacterial populations.Conversely, one of the gut microbiome’s key functions is to prevent the colonization and proliferation of both external pathogens and resident pathobionts, including bacteria resistant to antibiotics. This protection is mediated through mechanisms such as resource competition, metabolic interactions, and modulation of the host immune response. By limiting the colonization and expansion of resistant bacteria, the gut microbiome helps reduce the incidence of related infections and may contribute to lowering the overall burden of AMR. This review explores the dual role of gut microbiome in the dynamics of bacterial AMR, both as a reservoir for the emergence of AMR and a critical line of defense against its spread. The review also highlights key research gaps that need to be addressed to promote development of targeted microbiome-based strategies for combating bacterial AMR effectively.
Keywords: bacteria, antibiotics, antimicrobial resistance, gut microbiome, resistome